Peran Bidhumas Polda Sumbar Sebagai Penyebaran Informasi dan Fasilitator Komunikasi - Kurniawan, Deta Utama; Darwis, Yuliandre (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Public services by government agencies are currently receiving tremendous attention. One form of public service is the delivery of public information. In accordance with Law Number 14 of 2008 concerning Public Information Disclosure, every public agency must provide, submit and publish public information under its authority. In addition to conveying public information, government agencies are also required to listen to the aspirations of their public. To help organizations play both roles, government agencies need a public relations function. At Polda West Sumatera, the function assigned in this regard is Bidhumas Polda West Sumatera. The purpose of this study is to identify how the implementation of information dissemination activities, documentation information management and communication facilitators are implemented by Bidhumas Polda Sumbar. This research uses the constructivism paradigm, and a qualitative case study approach. Data were collected through observation, interviews, and documentation analysis conducted at Bidhumas Polda Sumbar. The results of this study indicate that the implementation of information dissemination, documentation information management and communication facilitators at Bidhumas Polda Sumbar has been running well